Answer:
x = -3
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Explanation:
Step 1: Define equation
5(x + 4) = -2(-4 - x) + 3
Step 2: Solve for x
- Distribute: 5x + 20 = 8 + 2x + 3
- Combine like terms: 5x + 20 = 2x + 11
- Subtract 2x on both sides: 3x + 20 = 11
- Subtract 20 on both sides: 3x = -9
- Divide 3 on both sides: x = -3
Step 3: Check
Plug in x to verify it's a solution.
- Substitute: 5(-3 + 4) = -2(-4 - -3) + 3
- Simplify: 5(-3 + 4) = -2(-4 + 3) + 3
- Add: 5(1) = -2(-1) + 3
- Multiply: 5 = 2 + 3
- Add: 5 = 5
Here we see that 5 does indeed equal 5. ∴ x = -3 is a solution of the equation.
And we have our final answer!